Intracellular Neutralization of Ricin Toxin by Single-domain Antibodies Targeting the Active Site. Issue 4 (14th February 2020) - Rudolph, Michael J.; Czajka, Timothy F.; Davis, Simon A.; Thi Nguyen, Chi My; Li, Xiao-ping; Tumer, Nilgun E.; Vance, David J.; Mantis, Nicholas J.
Abstract: The extreme potency of the plant toxin, ricin, is due to its enzymatic subunit, RTA, which inactivates mammalian ribosomes with near-perfect efficiency. Here we characterized, at the functional and structural levels, seven alpaca single-domain antibodies (VH Hs) previously reported to recognize epitopes in proximity to RTA's active site. Three of the VH Hs, V2A11, V8E6, and V2G10, were potent inhibitors of RTA in vitro and protected Vero cells from ricin when expressed as intracellular antibodies ("intrabodies"). Crystal structure analysis revealed that the complementarity-determining region 3 (CDR3) elements of V2A11 and V8E6 penetrate RTA's active site and interact with key catalytic residues. V2G10, by contrast, sits atop the enzymatic pocket and occludes substrate accessibility. The other four VH Hs also penetrated/occluded RTA's active site, but lacked sufficient binding affinities to outcompete RTA-ribosome interactions. Intracellular delivery of high-affinity, single-domain antibodies may offer a new avenue in the development of countermeasures against ricin toxin.toxin, antibody, structure, intracellular Graphical abstract: Image 1 Highlights: Ricin's catalytic subunit (RTA) inactivates ribosome with high efficiency. Alpaca single-domain antibodies (VHH) that target RTA's active site identified. Intracellular expression (intrabody) of VHHs neutralizes ricin toxin. Seven crystal structures of VHH-RTA complexes reported. Results pave the way for novel antitoxin therapies.